The Implantation of Kimbanguism in Kisangani, Zaire - MacGaffey, Wyatt (The Journal of African History, 1982)
Based on interviews with participants and witnesses, together with some documentation, the article describes the means and conditions by which Kimbanguist doctrines were introduced to Kisangani (Stanleyville) between 1945 and 1959, before the foundation of the Church of Christ on the Earth by the Prophet Simon Kimbangu as a national and international church. The special place in the covert theology of the Church of certain events in 1952, at the camp for Kimbanguist exiles in Lowa, is described. Discussion of ethnic rivalries during and after the foundation of the Church is related to the content of the oral traditions, which represent several political tendencies. The conclusion is that Kimbanguism in Upper Zaire differs from that of its place of origin in Lower Zaire in lacking roots in local culture and politics, and in having been primarily a product of nationalist sentiment after World War II.
Free